Meerkat and Tuba: design alternatives for randomness, surprise and serendipity in reminiscing - Helmes, John; O'Hara, Kenton; Villar, Nicolas; Taylor, Alex (Interact, 2011)
People are accumulating large amounts of personal digital content that play a role in reminiscing practices. But as these collections become larger, and older content is less frequently accessed, much of this content is simply forgotten. In response to this we explore the notions of randomness and serendipity in the presentation of content from people’s digital collections. To do this we designed and deployed two devices - Meerkat and Tuba - that enable the serendipitous presentation of digital content from people’s personal media collections. Each device emphasises different characteristics of serendipity that with a view to understanding whether people interpret and value these in different ways while reminiscing. In order explore the use of the devices in context, we deployed in real homes. We report on findings from the study and discuss their implications for design.